Fast tracking of hidden objects with single‐pixel detectors. Issue 15 (1st July 2017) - Chan, S.; Warburton, R.E.; Gariepy, G.; Altmann, Y.; McLaughlin, S.; Leach, J.; Faccio, D.
Abstract : A fast tracking system is demonstrated that is based on single laser illumination and a few single‐pixel single photon avalanche diode (SPAD) detectors that improves on the previous tracking of non‐line‐of‐sight motion by a factor of 300 in laser power. With an average illumination power of only 2 mW, a 15 cm ×15 cm object located up to 2.5 m away is tracked whilst outside of the direct line‐of‐sight and moving at approximately 6 cm/s.